Cutaneous paraneoplastic syndromes. Dermatological manifestations associated with malignancies - Polańska, Paulina; Gruszka, Marta; Zakrocka, Martyna; Kubicka, Maria (Journal of Education, Health and Sport, 2025)
Introduction and purpose: Paraneoplastic syndromes (PS) are conditions associated with malignant tumours whose mechanism of onset is not fully understood. It is postulated that it’s pathophysiology may involve metabolic, endocrine, haematological changes and autoimmune reactions. The aim of this study is to describe cutaneous PS that nearly always occur with neoplasms. The work aims to give an overview of their clinical manifestations and to indicate the neoplasms they are most commonly associated with. Description of the state of knowledge: Several types of cutaneous PS are almost always associated with malignancies. These include conditions like acroceratosis paraneoplastica, paraneoplastic pemphigus, erythema gyratum repens, acquired hypertrichosis lanuginosa, necrolytic migratory erythema, tripe palms, and syndromes such as AESOP syndrome, ectopic ACTH syndrome, and carcinoid syndrome. These dermatoses present a wide range of clinical features, including skin lesions that vary in appearance, severity, and location, and they are linked to different types of tumors. The connection between cutaneous PS and underlying neoplasms involves various potential pathophysiological mechanisms. However, the exact processes driving these relationships remain unclear and are the subject of ongoing research. Conclusions: Awareness of cutaneous PS is crucial for early malignancy detection. Timely identification of these skin manifestations allows for quicker diagnosis and treatment of underlying neoplasm, significantly improving the patient's prognosis.